Absorbierter organizational slack für die sekundäre Wertschöpfung - Krcal, Hans-Christian (Das Management des (un)erwünschten Ressourcenüberschusses., 2011)
The paper analyses the use of absorbed organizational slack in the context of its structure of value. The advantages of medium term use are being opposed to the short term reduction of slack. On the basis of the cost function elements it will be shown that instead of an optimal slack amount a performance adequate amount of slack is recommendable. Organizational slack can only be measured retrospectively. In the meantime, under the requirements of management, operational principles of resource management can actively contribute to a heuristic way of approaching the adequate point of slack. With the concept of so-called ‘secondary value added’ a kind of organizational structure has been drafted, which shows a possible use of absorbed organizational slack.